The Impact of product, Price, Distribution, Promotion, Location and Physical Evidence Against Purchasing Decisions On PT Prima Sahabat Mitra Bersama - Anita; Apriansyah Ramadani; Cordelia Khosasi; Acai Sudirman (International Journal Of Economics Social And Technology, 2023)
Study This aim for know influence product, Price, Distribution, Promotion, Location and Physical Evidence Against Purchasing Decisions at PT Prima Sahabat Mitra Bersama. This research uses quantitative and sample data types study a total of 97 samples were counted use formula lemeshow. Research results in a manner Partial showing that product own influence on Purchase Decision, price own influence on Purchasing Decisions, distribution own influence to Purchase Decision, promotion own influence on Purchase Decision, location own influence against Purchase Decision, evidence physique own influence to Decision Purchase. kindly simultaneous product, Price, Distribution, Promotion, Location And Proof Physique influential on Purchasing Decisions.